Is thrombotic event a side effect of oral buprenorphine abuse? Two case reports. Issue 4 (3rd March 2019) - Alirezaei, Toktam; Hajimoradi, Behzad
Key Clinical Message: Buprenorphine is used to treat opioid addiction. The spectrum of complications of oral buprenorphine is not well known. We describe two cases and based on a hypothesis is proposed which suggests that the use of oral buprenorphine could be relevant to the increase of thrombotic risk. Abstract : Buprenorphine is used to treat opioid addiction. The spectrum of complications of oral buprenorphine is not well known. We describe two cases and based on a hypothesis is proposed which suggests that the use of oral buprenorphine could be relevant to the increase of thrombotic risk.